Effectiveness of the Blessed Friday Program on Brand Awareness of Lazis Al-Haromain Kediri City Through Digital Marketing - Azizah, Siti Mufidatul; Zuraidah; Rahayu, Ana Duwi; Putri, Charista Tanta; Avifah, Nur (Jeksyah: Islamic Economics Journal, 2025)
This article analyzes effectiveness of the blaseed friday program on brand awereness of Lazis Al-Haromain Kediri City through digital marketing. This program utilizes social media, especially Instagram, to disseminate information and education about social activities carried out every Friday. The research method used is qualitative descriptive with a case study approach, with data collection through interviews, non-participant observations, as well as documentation from social media and internal reports of the institution. The results of the study show that the digital marketing strategy implemented has succeeded in increasing community involvement and the number of donors, which has an impact on the growth of donations and increasing public awareness of the existence of Lazis Al-Haromain Kediri City. In addition, transparency in the distribution of documented donations through social media has helped build public trust in this institution. While the program is effective, there are several challenges such as limited resources in content creation, limited operational funds for paid advertising, and changes in social media algorithms that affect the reach of uploads. Therefore, innovative strategies such as collaborating with influencers, social media optimization, and training digital marketing teams are solutions that can be applied to overcome these obstacles.